Device Closure of Perimembranous Ventricular Septal Defect Under Deep Sedation and Transthoracic Echo Guide: A Case Report - Fatema, NN; Rashid, H; Azad, AK (Cardiovascular Journal, 2010)
T, an eight years old girl was diagnosed as a case of perimembranous Ventricular Septal Defect (VSD) since 6 months of her age. She had recurrent chest infection since early infancy. Her Echocardiography with colour Doppler showed a 4.5 mm perimembranous VSD which was 5 mm away from the aortic valve. As pulmonary artery pressure was normal, she was kept under follow up and device closure was planned. At last she was taken into the catheterization laboratory of combined military Hospital, Dhaka on 1st July 2008 and VSD was closed with an 8 mm Amplatzer perimembranous VSD device. Whole procedure was done under deep sedation with Ketamine and transthoracic echocardiography (TTE) and fluroscopy guide. It is the first ever case of VSD device closure where procedure was done under sedation and TTE guide which lead to the writing of this report. Keywords: VSD; Transthoracic Echo; Amplatzer Device. DOI: 10.3329/cardio.v3i1.6432 Cardiovasc. j. 2010; 3(1): 89-91